The Mourning Process from Shattering to Integration - Iacob, Diana Alexandra (New Trends in Psychology, 2024)
Grief is the process by which the experience of loss and the pain associated with it are integrated at a psychological level and whose completion allows the person to reorient themselves towards life, a world and a life that no longer include the deceased person. The loss of a loved one is a natural event in the course of life and is at the same time one of life’s greatest challenges. The death of a loved one is a major stressor for at least two main reasons: loss (the sudden break in the attachment relationship) and the confrontation with the theme of death, perhaps one of man’s greatest fears.